1995
DOI: 10.1165/ajrcmb.12.2.7532419
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor stimulates DNA synthesis in alveolar epithelial type II cells in vitro.

Abstract: Hepatocyte growth factor (HGF) and its receptor, the product of c-MET proto-oncogene, are highly expressed in both fetal and adult lung, though their physiologic functions in the lung are largely unknown. In the present study, we examined whether alveolar type II cells in the lung are the target of HGF and whether HGF has any effects on growth of these cells. The alveolar epithelial type II cells were isolated from the lungs of adult male Sprague-Dawley rats by elastase digestion, and the cells were used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…Evidence is accumulating that HGF stimulates proliferation of bronchial and alveolar type II epithelial cells through DNA synthesis in vivo as well in vitro (16,17,33,34). Moreover, Yamada et al (25) demonstrated that the neutralization of HGF strongly inhibited DNA synthesis of alveolar epithelial cells in the ischemic-reperfused lung injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is accumulating that HGF stimulates proliferation of bronchial and alveolar type II epithelial cells through DNA synthesis in vivo as well in vitro (16,17,33,34). Moreover, Yamada et al (25) demonstrated that the neutralization of HGF strongly inhibited DNA synthesis of alveolar epithelial cells in the ischemic-reperfused lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Intratracheal and i.v. administration of recombinant HGF stimulates DNA synthesis of alveolar type II cells in the rat lung after acute lung injury (16,17). Moreover, exogenously administered HGF attenuated bleomycininduced lung fibrosis in mice (18).…”
mentioning
confidence: 99%
“…37,38 It stimulates DNA synthesis 39,40 and proliferation of alveolar type II epithelial cells, 41 thus contributing to regeneration of alveolar structures following injury. Previous studies have also shown that administration of exogenous HGF via systemic 20 or intratracheal route 19 into bleomycin-injured mice resulted in the reduction of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage lineage cells promote tissue repair by producing potential growth factors such as hepatocyte growth factor or HGF (25,26). HGF is a mitogen for various types of epithelia, including bronchial and alveolar epithelial cells (27,28). Recombinant HGF augments DNA synthesis of alveolar type II cells in acute lung injury, and also reduces pulmonary fibrosis during bleomycin-mediated lung injury (29).…”
Section: Clinical Relevancementioning
confidence: 99%